The impact of uro-oncology multidisciplinary team meeting (MDTM) on clinical decision-making and adherence to MDTM recommendation: experience from a tertiary referral centre in Malaysia - Norshuhada Amat; Lim Jeffery; Chai C. Ann; Yeoh W. Sien; Ahmad N. Fadzli; Shanggar Kuppusamy; Marniza Saad; Ong T. Aik (African Journal of Urology, 2024)
Abstract Background Multidisciplinary team meeting (MDTM) has become an increasingly important part of disease management model, particularly in cancer care. MDTM consists of a group of doctors to provide independent opinions on diagnostic and treatment decisions, as well as personalized therapeutic plan for patients. By selecting the most suitable treatment for patients from multiple perspectives, management by multidisciplinary team (MDT) have been shown to have advantages over traditional treatment models. The objective of this study is to determine the impact of MDTM on the management of uro-oncological cases and adherence to MDTM plans. Methods We retrospectively collected patients’ clinical information discussed in MDTM from 1st January 2021 to 31st December 2022 at our institution. The pre-MDTM treatment plan by the clinicians and the MDTM consensus plans were compared to assess the overall MDTM impact on patient management. Adherence to MDTM recommendations was also analyzed. Results Data on 432 patients discussed in MDTM from 1st January 2021 to 31st December 2022 were collected and analyzed. Prostate cancer was the most common type of cancer discussed (n = 212, 48.8%). MDTM had a significant impact on decision-making in 276 (63.6%) cases, with changes to patient management being observed in more than half of all cases. Adherence to MDTM outcomes was high with 383 (90.5%) of patients eventually had treatment according to the MDTM recommendation. Conclusion The study highlights the importance of MDTM in the management of genitourinary malignancies, particularly in cases where no original plan exists. Patient’s compliance and adherence to the MDTM consensus plan are also very encouraging.